Fancy nancy and the mean girl eaudiobook - O'Connor, Jane (I Can Read, Level 1: Fancy Nancy, 2011)
Nancy will have to do some fancy footwork to resolve her predicament in this latest Fancy Nancy story from the beloved New York Times bestselling author-illustrator team Jane O'Connor and Robin Preiss Glasser. Much to her dismay, Nancy has been chosen for the relay team in this year's Field Day at school. Despite her many natural talents, Nancy isn't much of a runner. She's afraid of letting her team down—especially after finding out that an unkind (that's another word for mean) girl in her class is on the team too. With a little help from her dad, Nancy tries her best, stands up for herself, and makes a new friend. Fancy Nancy and the Mean Girl is a Level One I Can Read book, which means it's perfect for children learning to sound out words and sentences. The back matter features a list of the rich vocabulary words that are used throughout the story along with their definition.